Exploratory serum fatty acid patterns associated with blood pressure in community-dwelling middle-aged and elderly Chinese. Issue 1 (December 2016) - Yang, Bo; Ding, Fang; Yan, Jing; Ye, Xiong-Wei; Xu, Xiao-Lin; Wang, Feng-Lei; Li, Duo; Yu, Wei
Abstract Background Epidemiological studies have assessed relationships between circulating levels of fatty acid (FA) and blood pressure (BP), and their results remain controversial. Nevertheless, data are sparse on serum FA as biomarker and BP in China. The aim of the study was to investigate the association between serum FA and BP in Chinese populations. Methods We conducted a cross-sectional study nested within a community-based cohort of 2447 Chinese participants aged 35–79 years who completed a baseline assessment between October 2012 and April 2013. Baseline assessment included the collection of fasting blood samples, anthropometric measurements and a personal interview using a validated questionnaire. Serum FA was determined by gas-liquid chromatography. Exploratory factor analyses were employed to identify FA-factor as a reflection of serum FA pattern. A multiple regression model was conducted to estimate adjusted mean of BP with 95 % confidence interval (CI) by tertile groups of the generated FA-factor scores. Results Hypertensive patients have significantly higher serum 14:0, 16:0, 16:1n-7, 18:3n-6, 20:3n-6 and Δ6 -desaturase index (18:3n-6/18:2n-6) as well as lower 18:2n-6, 22:6n-3 and Δ5 -desaturase index (20:4n-6/20:3n-6) compared with normotensive participants. Factor 1 (low linoleic acid/high saturated FA pattern: 14:0, 16:0, 16:1n-7, 18:2n-6, 18:3n-6, 20:3n-6) and Factor 2 (n-3 PUFA pattern: 20:5n-3, 22:5n-3, 22:6n-3, 18:1n-9) were identified as indicators of the serum FA pattern. After adjustment for age, gender, body mass index, hypertension treatment, smoking, alcohol intake, education, profession, exercise habit, salt intake, family history of hypertension, heart rate, blood lipids and fasting blood-glucose levels, per a standard deviation (SD) increment of Factor 1 scores was associated with an increment of 2.44 (95 % CI: 1.73, 3.15) mm Hg for systolic BP, whereas per a SD increment of Factor 2 scores was associated with a reduction of 1.40 (95 % CI: 0.80, 2.04) mm Hg for diastolic BP. Conclusions The serum FA pattern characterized by low proportions of 14:0, 16:0, 16:1n-7 and 18:3n-6 as well as high 18:2n-6 and 22:6n-3 was beneficially associated with BP levels in this Chinese population. This evidence well supports the current dietary recommendations in the communities to replace saturated fat with polyunsaturated fat.